Eradication of high viable loads of Listeria monocytogenes contaminating food-contact surfaces - de Candia, Silvia; Morea, Maria; Baruzzi, Federico (Frontiers in Microbiology, 2015)
This study demonstrates the efficacy of cold gaseous ozone treatments at low concentrations in the eradication of high Listeria monocytogenes viable cell loads from glass, polypropylene, stainless steel and expanded polystyrene food-contact surfaces. Using a step by step approach, involving the selection of the most resistant strain-surface combinations, 11 Listeria spp. strains resulted inactivated by a continuous ozone flow at 1.07 mg m-3 after 24 or 48 h of cold incubation, depending on both strain and surface evaluated. Increasing the inoculum level to 9 log CFU coupon-1, the best inactivation rate was obtained after 48h of treatment at 3.21 mg m-3 ozone concentration when cells were deposited onto stainless steel and expanded polystyrene coupons, resulted the most resistant food-contact surfaces in the previous assays. The addition of naturally microbiologically contaminated meat extract to a high load of L. monocytogenes LMG 23775 cells, the most resistant strain out of the 11 assayed Listeria spp. strains, led to its complete inactivation after four days of treatment. To the best of our knowledge, this is the first report describing the survival of L. monocytogenes and the effect of ozone treatment under cold storage conditions on expanded polystyrene, a commonly-used material in food packaging. These results could be useful for reducing pathogen cross-contamination phenomena during cold food storage.